(untitled) (Nepal Medical College Journal, 2024)
Objective structured clinical examination (OSCE) is a valuable assessment tool that enhances in-depth learning and preparation of students for clinical practice. The tasks to be assessed should be of different types and of varying difficulties. The tasks in OSCE depend on the level of students training. The aim of the study was to assess the perception of OSCE among under-graduates’ medical students. A mixed methods study (cross sectional exploratory and content analysis) was conducted with the simple random sampling, purposive sampling and content analysis technique among 86 undergraduates’ medical students at tertiary hospital. SPSS 16 was used for data entry. Frequency, percentage, Mean, Standard deviation, Mann-Whitney U-test and One Way Anova was used for data analysis. Most of the participants perceived that OSCE identified knowledge gaps (84.8%) and was educative (79.0%). There was no significant difference of perception of OSCE related to gender. There was no significant variation in participant’s perceptions of OSCE in relation to academic year regarding OSCE domain characteristics (p =0.333). However, regarding perception of OSCE domain structure in relation to their academic year, there was a significant difference as p =0.013. The overall perception of OSCE among medical students was positive. This study has identified a need for training, practice prior to an OSCE exam and allocation of adequate timefor each spot during the exam.